Menangani cabaran wanita melalui kajian wacana hadis nabawi - Abdullah Ariza, Abdul Jabar Mohd Azidan, Mustapha Nik Farhan, Toklubok@Hajimaming Pabiyah (Universiti Pendidikan Sultan Idris, 2016)
Menangani cabaran wanita melalui kajian wacana hadis nabawi by Abdullah Ariza, Abdul Jabar Mohd Azidan, Mustapha Nik Farhan, Toklubok@Hajimaming Pabiyah,